Comparing Digital and Traditional Reading for Pleasure: Effects on 11th Graders' Comprehension - EL HADDAD, RANYA AHMED AREF
This study investigates the impact of the Reading for Pleasure (RfP) program on 11th-grade students' reading comprehension in private schools in Ajman, UAE, comparing digital and printed reading mediums. It explores how students’ preferences for these formats influence their reading engagement and comprehension. Grounded in theories of reading comprehension and second language acquisition (SLA), the research uses a mixed-methods approach, incorporating quantitative assessments from a quasi-experiment and qualitative insights from a survey and a focus group interview. Findings show that while both digital and printed formats positively affect comprehension, printed texts consistently foster deeper cognitive engagement, particularly with complex reading tasks. Students expressed a preference for printed materials for their ability to minimize distractions and enhance focus, whereas digital formats were favored for accessibility and ease of use in shorter tasks. The study recommends a balanced integration of both mediums, supporting student choice and improving digital literacy skills. By blending the strengths of digital and printed texts, educators can better cater to diverse learning preferences. The research contributes to theoretical frameworks on cognitive engagement in reading and SLA, while offering practical recommendations for curriculum designers and educators in ESL contexts. Additionally, the study highlights the need for future research on the long-term effects of medium preferences and gender differences in reading outcomes.